You need to evaluate the following logarithm `log_5 (0+1) - 3` , such that:

`log_5 (0+1) = log_5 1`

Since `log_5 1 = 0` yields:

`log_5 (0+1) - 3 = 0 - 3 = -3`

You may also evaluate the expression, such that:

`log_5 (0+1) - 3 = log_5 1 - 3*1`

Replace `log_5 5` for 1, such that:

`log_5 (0+1) - 3 = log_5 1 - 3*log_5 5`

Use the power property of logarithms, such that:

`log_5 (0+1) - 3 = log_5 1 - log_5 5^3`

Converting the difference of logarithms into the logarithm of quotient yields:

`log_5 (0+1) - 3 = log_5 1/(5^3)`

`log_5 (0+1) - 3 = log_5 (5^(-3)) `

Taking out the power of argument yields:

`log_5 (0+1) - 3 = -3log_5 5 = -3*1 = -3`

**Hence, evaluating the given expression containing logarithms, yields **`log_5 (0+1) - 3 = -3.`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now